Histopathological Findings in Cynomolgus Macaques (Macaca fascicularis) Consistent with Secondary Immunological Reaction to Biotherapeutics with an Emphasis on the CNS and Eye. (February 2019) - Naylor, Stuart W.; Czajkowski, Melissa; Harvey, Warren; Smith, Matt; Bradley, Alys E.; Cary, Maurice
Biotherapeutics are pharmaceutical products derived from or synthesized by biological systems. Such molecules carry the potential for immunogenicity which may lead to adverse immune responses. The cynomolgus macaque ( Macaca fascicularis ) is the species of choice in nonclinical safety assessment of biotherapeutics. The main aim of this study was to confirm whether mononuclear cell infiltrates at specific locations represent a generic effect of biotherapeutics, and therefore the result of their immunogenicity. Following a review of microscopic findings in studies conducted over a 10-year period at one test facility, 15% of biotherapeutics were reported to have such findings. The most commonly affected site was the choroid plexus and less frequently the meninges and ciliary body. The reporting of such findings as test article–related becomes more subjective as the severity and incidence decreases. To assess the accuracy of such associations, a mathematical approach was employed to determine the probability of obtaining the observed results by chance. There was good agreement between this approach and the original findings. In addition to an increased number and size of mononuclear cell infiltrates in the brain, biotherapeutic administration was strongly associated with the presence of plasma cells and eosinophils.